SOSIALISASI NILAI BUDAYA DALAM KELUARGA (KASUS: PADA KELUARGA YANG MEMPUNYAI ANAK BERPERILAKU MENYIMPANG DARI NILAI BUDAYA DI DESA CIMPUNGAN , KECAMATAN SIBERUT TENGAH KABUPATEN KEPULAUAN MENTAWAI) - Lempe, Faleria - (Pendidikan Sosiologi, 2014)
In Desa Cimpungan Kecamatan Siberut Kabupaten Kepulauan Mentawai, the cultural values were socialized hereditarily from older generation (punuteteu) to the young generations. Based on the research findings, it was figured out that the socialization process ideally occurred when the children were between 0-10 years old. When they were teenagers, in order to help the children able to do adaptation with their environment, parents told their children about what should and should not be done. The parents advised them in a leisure time or when they sat together with their family. Unfortunately, the parents were busy with their works and had less communication with their children so that they had lack of understanding on cultural values. This then made the children had deviant behaviors. The parents should control their attitudes and forbid them from uttering bad words. This research was intended to describe: (1) the family background of the children with deviant behaviors in Desa Cimpungan, (2) the socialization of cultural values in families in Desa Cimpungan.This was a case study which applied qualitative approach. The informants of the research were chosen by using purposive sampling technique. The data was collected through observation and interview. The data gotten then was analyzed, reduced, presented and conclusions were drawn. To conduct this research, the socialization theory for children written by George Herbert Mead was applied.The result of the research indicated that there were four families in Desa Cimpungan having children with deviant behaviors. The deviances were: the first family had a child getting married with a person from similar clan, the second family had a child rapping young child, the third family had a child with stealing case, and the fourth family had a child getting pregnant without marriage. There were two kinds of socialization of cultural values in a family covering:1. The socialization of non-materials cultures in which parents teach children about traditional rules, worship ordinances and building friendship.2. The socialization of materials cultures including technology of communication, household tools, hunting equipments, and fishing equipments.The ones who mainly had a duty to introduce cultural values to the children were parents and people from fatherâs family. The facts, however, showed that the children had deviant behaviors. They then were fined based on the rules and norms applied in Desa Cimpungan.